Gadgets in the Gymnasium: Physical Educators' Use of Digital Technologies | Les gadgets au gymnase : l'utilisation des technologies numériques par les enseignants en éducation physique - Daniel Robinson; Lynn Randall (The Canadian Network for Innovation in Education (CNIE), 2017)
This article highlights results from a recent study that investigated Atlantic Canadian physical educators' adoption and implementation of various digital technologies. Employing a mixed-methods research design (survey participants, n = 206; focus group participants, n = 12), the research intended to provide a clear overview of physical educators' implementation of digital technologies-as well as an account of the factors that may enable or limit their use. Results suggest that some digital technologies are used more (e.g., audio players, computers) than others (e.g., Dartfish, iTouch). Moreover, a number of external barriers (limitations in time, expertise, resources) and internal barriers (teacher beliefs, established pedagogy) were identified. In light of these results, a number of observations and comments are offered. Results from this research might be of particular interest to those engaged with physical education and technology implementation. Cet article souligne les résultats d'une étude récente qui s'est penchée sur l'adoption et la mise en application de diverses technologies numériques par les moniteurs d'éducation physique du Canada atlantique. À l'aide d'un modèle de recherche faisant appel à des méthodes mixtes (participants au sondage, n = 206; participants au groupe de discussion, n = 12), l'étude entendait fournir un survol limpide de la mise en œuvre des technologies numériques par les enseignants en éducation physique, ainsi qu'un compte-rendu des facteurs qui peuvent permettre ou limiter cet usage. Les résultats suggèrent que certaines technologies numériques sont plus utilisées (p. ex. lecteurs audio et ordinateurs) que d'autres (p. ex. Dartfish, iTouch). De plus, un certain nombre d'obstacles externes (des limites relatives au temps, à l'expertise, aux ressources) et internes (croyances des enseignants, pédagogie établie) ont été repérés. À la lumière de ces résultats, nous offrons certaines observations et des commentaires. Les résultats de ces recherches peuvent être intéressants pour les personnes qui s'occupent de l'éducation physique et de la mise en application des technologies.